Dari Demokrasi ke Undi: Tinjauan Teologis tentang Undi dalam Alkitab serta Relevansinya bagi Pemilihan Pemimpin Gereja - Rut Debora Butarbutar; Raharja Milala; Jeimme Ulin Tarigan (KENOSIS: Jurnal Kajian Teologi, 2020)
Democracy is a leader election system in the political world that adopted by the church system, especiallyÂ  the tribal church based in North Sumatra, to elect the leader of the synod. The system with the most votes, caused the election of synod leader to be coloured by negative issues and actions that hurt the nature of the church. For this reason, this paper offers the lot as an alternative system for electing synod leader. This research uses biblical text analysis with a narrative interpretation approach. The text will be analyzed by paying attention to the meaning and execution system of the lot. Interpretation will be made on 1 Samuel 10: 1-27 from the Old Testament and Acts 1:15-26 from the New Testament. The results of the analysis show that the lot is a leader election system in the biblical tradition and can be used as a new model for choosing a synod leader, particularly churches that are still implementing a democratic system. The lot is a representation of God's election, which is carried out in a confidential, fair and honest manner so as to avoid negative practices and issues in the election of the leader of the synod.AbstrakDemokratis merupakan sistem pemilihan pemimpin dalam dunia politik yang diadopsi oleh gereja, khususnya gereja suku yang berpusat di Sumatera Utara, untuk memilih ketua sinode. Sistem dengan penentuan suara terbanyak, menyebabkan pemilihan ketua sinode kerap diwarnai isu dan tindakan negatif yang mencederai hakikat gereja. Sehubungan dengan itu, tulisan ini menawarkan undi sebagai alternatif sistem pemilihan ketua sinode. Penelitian ini menggunakan analisis teks Alkitab dengan pendekatan penafsiran naratif. Teks akan dianalisis dengan memperhatikan pemaknaan dan sistem pelaksanaan undi. Penafsiran akan dilakukan terhadap 1 Samuel 10:1-27 dari Perjanjian Lama dan Kisah Para Rasul 1:15-26 dari Perjanjian Baru. Hasil analisis menunjukkan bahwa undi merupakan sebuah sistem pemilihan pemimpin yang terdapat dalam tradisi Alkitab dan dapat dijadikan sebagai model baru dalam memilih ketua sinode, khususnya gereja yang masih melakukan sistem demokratis. Undi merupakan representasi pemilihan Allah yang pelaksanaannya bersifat rahasia, adil dan jujur, sehingga dapat menghindarkan praktik dan isu negatif dalam pemilihan ketua sinode.Â